Hemorrhagic varicella - S Nageswaramma; G Swarna Kumari; Bala Kumar Dorai (Wolters Kluwer Medknow Publications, 2018)
Varicella is a benign disorder occurring commonly in children. Hemorrhagic varicella is a serious complication occurring in immunocompromised persons or those on immunosuppressive therapy. Our encounter with this case of Hemorrhagic varicella highlights that the rare hemorrhagic varicella can also occur in a chronic malnourished child. Prompt diagnosis and treatment with acyclovir leads to complete recovery.